Influence of Transition Metal Ion Doping on the Crystallization and Photocatalytic Activity of TiO2 Prepared Via Adsorption Phase Synthesis - Wang, Ting; Zhu, Yingyan; Wu, Xinxin; Yang, Caihong; Cao, Yongqiang; Wu, Liguang (Current Nanoscience, 2014)
TiO2 photocatalysts doped with three transition metal ions of varying concentration were prepared by adsorption phase synthesis. The influence of different metal ion species and contents on the morphology and crystallization of TiO2 sintered under various temperatures was explored by transmission electron microscopy, X-ray diffractometry, UVvis spectroscopy, and X-ray photoelectron spectroscopy. Photodegradation experiments on methyl-orange were employed to evaluate photocatalytic activity. Results indicated that 0.05 at.% Fe3+ and Cd2+ doping introduces lattice distortions as shallow trapping sites; moreover, doping improved the activity of adsorption phase synthesis (APS) catalysts. TiO2 crystallization was restricted when the doping content was greater than 0.05 at.% because other metal ions destroy the TiO2 lattice structure. Restriction also increased with doping content. An optimum doping content was observed during the preparation of TiO2 doped with Cd2+ and Fe3+. As the Fe3+ radius is close to the Ti4+ radius, the influence of Fe3+ doping content on TiO2 crystallization and activity was more apparent than that of Cd2+ doping content. Increases in sintering temperature resulted in fewer lattice distortions acting as shallow trapping sites and decreases in APS catalyst activities.
Keywords: photodegradation